Perbandingan Perhitungan BoQ antara Revit 2019 dengan Dokumen Perencanaan pada Pekerjaan Non Struktur - Zumarnis, Putri Ferira; Husni, Hasti Riakara; Bayzoni; Siregar, Amril Ma’ruf (REKAYASA: Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2024)
The development of science and technology that is increasingly sophisticated, is currently known for a new technology in the field of construction, namely Building Information Modeling (BIM). BIM is a planning process that includes all project data and information that can be efficiently implemented in 3D. Therefore, this study aims to conduct a study on the use of BIM by modeling non-structural elements using BIM-based software, namely Autodesk Revit 2019 and comparing the results of calculating the volume of non-structural work performed obtained from Autodesk Revit 2019 on planning documents. The case study used in this research is Building G, Faculty of Agriculture, University of Lampung. From the results of the modeling and calculations that have been carried out, there is a significant difference between the BoQ calculations using Revit 2019 and the existing planning documents. The following is a breakdown of the percentage comparison of the results of the BoQ calculations using Revit 2019 to the planning documents, namely plastering and plastering work by 17.89% , 20.64% of rocktile km/wc ceramic work, 4.65% of door work, 17.65% of window work, and 6.93% of ceiling work. From this research it can be concluded that modeling non-structural elements using Autodesk Revit 2019 can be done easily and a more accurate and fast BoQ calculation is obtained.